Pengaruh Kompensasi dan Peran Serikat Pekerja terhadap Kepuasan Kerja Serta Dampaknya terhadap Produktivitas Karyawan PT. DEW Indonesia - Nopi Oktavianti; Yusni Nuryani; Nariah Nariah (Ekonomis: Journal of Economics and Business, 2022)
The purpose of the study was to determine the partial and simultaneous effect of compensation and the role of trade unions on employee job satisfaction, to determine the effect of job satisfaction on productivity and to determine the partial and simultaneous effect of compensation and the role of trade unions on productivity. This study uses quantitative methods. The population in this study were all employees of PT. Indonesian DEW. While the sample used in this study is a saturated sample of 80 respondents. Data collection techniques by means of questionnaires and data analysis techniques using instrument test, classical assumption test, path analysis, t-test and F-count test. The results of the study show that there is an effect of compensation on employee job satisfaction, there is an influence of the role of the union on employee job satisfaction, there is an influence between compensation on employee work productivity, there is an influence of the role of the union on employee work productivity, there is an influence of job satisfaction on employee work productivity, there are the effect of compensation and the role of unions simultaneously on employee job satisfaction, there is an influence between compensation, the role of unions and job satisfaction simultaneously on employee work productivity.